Diverse Mesozoic thrips carrying pollen during the gymnosperm-to-angiosperm plant-host ecological shift - Enrique Peñalver; Constanza Peña-Kairath; Eduardo Barrón; Patricia Nel; André Nel; Xavier Delclòs; David Peris; Mónica M. Solórzano-Kraemer; Ana Rodrigo (iScience)
Summary: Insects are important pollinators, and entomophilous pollination of gymnosperms occurred long before the Cretaceous radiation of angiosperms, but most extant pollination systems involve angiosperms. We studied four thrips of the extinct genus Tethysthrips present in Albian (Early Cretaceous) Spanish amber, one of which carried a patch of gymnosperm Cycadopites pollen grains, some of them attached around the mouthparts, providing direct fossil evidence of pollinivory and pollination. We describe the new species Tethysthrips attenboroughi, which belongs to the extant family Thripidae (suborder Terebrantia). In addition, we studied a Cycadopites pollen load in one specimen belonging to stem group Phlaeothripidae (suborder Tubulifera), from Cenomanian Burmese amber. This illustrates an ancient stage of gymnosperm plant host that most likely favored the later stage involving angiosperms. The absence of extant pollinators of gymnosperms in Thripidae and Phlaeothripidae, and in the terebrantian family Melanthripidae, which contain Cretaceous pollinators of gymnosperms, indicates impoverishment in their gymnosperm relationship.